One hundred and fifty years of Coulomb stress history along the California‐Nevada border, USA. Issue 2 (3rd February 2015) - Verdecchia, Alessandro; Carena, Sara
Abstract: The region north of the Garlock Fault between the Sierra Nevada and Death Valley has experienced at least eight Mw  ≥ 6 earthquakes in historical times, beginning with the 1872, Mw 7.5, Owens Valley earthquake. Furthermore, since 1978, the Long Valley Caldera has been undergoing periods of unrest, with earthquake swarms and resurgence. Our goal is to determine whether the 1872 Owens Valley earthquake and the caldera unrest have influenced the evolution of seismicity in the area. We model the evolution of coseismic, postseismic, and interseismic Coulomb stress change (Coulomb failure stress (ΔCFS)) in the region due to both Mw  ≥ 6 earthquakes and caldera inflation in the last 150 years. Our results show that the 1872 Owens Valley earthquake has an important influence on subsequent events, strongly encouraging faulting in northern Owens Valley while inhibiting it elsewhere. There is also a correlation between caldera inflation and seismicity in northern Owens Valley, evidenced by the west‐to‐east migration of earthquakes from the Long Valley Caldera toward the White Mountains immediately following the 1978 caldera inflation event. Finally, we show that a total ΔCFS increase of up to 30 bars in the last 150 years has occurred on part of the White Mountains fault, making it a possible candidate for the next major earthquake in this region. Key Points: The 1872 Owens Valley earthquake controlled subsequent seismicity distribution Caldera inflation influenced seismicity in northern Owens Valley White Mountains fault may be close to failure